The very rare Japanese endemic diving beetle Japanolaccophilus niponensis (Kamiya, 1939), (Coleoptera: Dytiscidae, Laccophilinae): larval morphology and phylogenetic comparison with other known Laccophilini - Alarie, Yves; Watanabe, Kohei; Michat, Mariano C. (Zootaxa, 2023)
The three larval instars of Japanolaccophilus niponensis (Kamiya, 1939) (Coleoptera: Adephaga, Laccophilinae) are described for the first time according to the now genevralized larval descriptive format of Dytiscidae (Coleoptera: Adephaga), which incorporates detailed chaetotaxic and morphometric analyses. A parsimony analysis based on larval characteristics of 14 Laccophilini species in seven genera was conducted using the program TNT. One of the main results is that Japanolaccophilus Satô, 1972, which so far was treated as being related to Neptosternus Sharp, 1882 now stands out as sister to Laccophilus Leach, 1815, and Philodytes J. Balfour-Browne, 1938 with strong support. Additionally, Laccomimus Toledo & Michat, 2015, and Africophilus Guignot, 1948 are resolved as monophyletic and sister to a clade which itself is subdivided into two well supported clades: Neptosternus + Australphilus Watts, 1978, and Japanolaccophilus + (Laccophilus, Philodytes). Philodytes is here newly accepted as junior synonym of Laccophilus.